2017
DOI: 10.3390/su9050862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clean Air Act on Patenting Activities in Chemical Industry: Learning from Past Experiences

Abstract: Abstract:The chemical industry provides essential goods we use in our daily lives and key ingredients for many diverse industries. On the other hand, their production and use require serious attention while they may be seriously harmful to local air quality. The Clean Air Act (CAA) and its subsequent amendments regulate the emissions of hazardous air pollutants to protect public health and welfare in the U.S.A. since 1970. This study aimed to assess the impact of CAA on the rate of patenting in the chemical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The influence of The Clean Air Act on the volume of patenting in the chemical sector was studied using basic chemical utility patents to identify the impacts of the Act on patenting activities. Following fitting the Autoregressive Integrated Moving Average model, a significant outlier was discovered, concluding that the chemical sector reacted to changes extremely efficiently (Durmuşoğlu, 2017). Based on the results of an analysis comparing Holt-Winters Exponential Smoothing with an Autoregressive Integrated Moving Average model for technology change forecasting using USPTO patent data from 1996 to 2013, Holt-Winters Exponential Smoothing outperformed Autoregressive Integrated Moving Average (Smith and Agrawal, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of The Clean Air Act on the volume of patenting in the chemical sector was studied using basic chemical utility patents to identify the impacts of the Act on patenting activities. Following fitting the Autoregressive Integrated Moving Average model, a significant outlier was discovered, concluding that the chemical sector reacted to changes extremely efficiently (Durmuşoğlu, 2017). Based on the results of an analysis comparing Holt-Winters Exponential Smoothing with an Autoregressive Integrated Moving Average model for technology change forecasting using USPTO patent data from 1996 to 2013, Holt-Winters Exponential Smoothing outperformed Autoregressive Integrated Moving Average (Smith and Agrawal, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, through "(A) Time Series Analysis (TSA)", the frequency of patent applications by technology was extracted as time series data to predict promising future technology [21,24,[28][29][30][31]34,[38][39][40][41][42][43][44]. Then, through "(B) Social Network Analysis (SNA)", the relationship between nodes as a quantitative indicator through centrality indices was extracted, and promising detailed descriptive areas based on the extracted indicators were predicted [22,[24][25][26][27][28][29][30][31][32]34,39,40,43,[45][46][47][48][49][50]. In addition to the quantitative analysis methods, the qualitative analysis method of "(C) Technology Mapping Analysis (TM)" was also used in previous studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the quantitative analysis methods, the qualitative analysis method of "(C) Technology Mapping Analysis (TM)" was also used in previous studies. Through "(C) Technology Mapping Analysis (TM)", the importance of the level of technology for each area was obtained, and priorities for technology development were identified [21,24,[29][30][31]38,40,[45][46][47][48][49][50][51]. In addition to predicting promising technology, previous studies have identified vacant technology by analyzing patent information of analysis target nodes through "(D) Generative Topographic Mapping Analysis (GTM)", identifying empty technology [24,27,28,40,52].…”
Section: Literature Reviewmentioning
confidence: 99%
“…de Araújo et al (2007) proposed a method that selects the most accurate prediction model first and then performs a behavioral statistical test and a phase fix procedure to adjust the time phase distortions that appear in financial time series. Durmuşoğlu (2017) used outlier analysis to check whether there is a need for an update of the forecasting model on hand.…”
Section: Related Workmentioning
confidence: 99%